Pelatihan Pemanfaatan Manajemen Referensi Zotero - Nurul Izzah; Rini Hayati Lubis (STMIK Royal, 2021)
Abstract: Training on the use of Zotero reference management aims to improve the ability of students of the Faculty of Economics and Islamic Business to use the Zotero application in writing their thesis. This activity is based on the needs of students in managing references and citations used in completing scientific papers or theses. The training method is carried out in several stages starting from planning, implementation, and evaluation. More training is carried out starting with the explanation of the material and continuing with practical activities. The results of this training indicate that the ability of students who take part in the training increases in using the Zotero application. The ability of students also increases in managing references and determining appropriate references to be cited in scientific papers.Keywords: reference management; training; ZoteroAbstrak : Pelatihan pemanfaatan manajemen referensi Zotero bertujuan untuk meningkatkan kemampuan mahasiswa Fakultas Ekonomi dan Bisnis Islam dalam menggunakan aplikasi Zotero dalam penulisan skripsi. Kegiatan ini didasari oleh kebutuhan mahasiswa dalam mengelola referensi dan sitasi yang digunakan dalam menyelesaikan karya ilmiah atau skripsi. Metode pelatihan dilakukan dengan beberapa tahapan yang dimulai dari perencanaan, pelaksanaan dan evaluasi. Pelatihan lebih dilakukan dimulai dengan penjabaran materi dan dilanjutkan dengan kegiatan praktek. Hasil pelatihan ini menunjukkan bahwa kemampuan mahasiswa yang mengikuti pelatihan meningkat dalam memanfaatkan aplikasi Zotero. Kemampuan mahasiswa juga semakin meningkat dalam mengelola referensi serta menentukan referensi yang tepat yang akan disitasi dalam karya ilmiah. Kata Kunci : manajemen referensi; pelatihan; Zotero